PENGARUH DESAIN ARSITEKTUR TERHADAP PERILAKU PENGGUNA DI GEDUNG LABORATORIUM TEKNIK SIPIL DAN GEDUNG C2-C3 UNIVERSITAS NEGERI GORONTALO - Syafriyani; Heryati; Fitrah (Jurnal Ilmu Teknik Terapan, 2025)
This study aims to analyze the impact of architectural design on user behavior in the Civil Engineering Laboratory Building and Buildings C2 and C3 at the Faculty of Engineering, Gorontalo State University. Data were collected through direct observation, site surveys, and interviews with space users. The results showed that space design, considering thermal comfort, circulation layout, and social spaces, significantly influenced students' academic and social behaviors. However, challenges such as limited social spaces and inadequate ventilation systems affected comfort and interaction. The study also provides recommendations to improve design, such as adding green elements, expanding social spaces, and optimizing ventilation systems. These changes are expected to create a more sustainable environment, support better social interactions, and increase user productivity.